The impact of age on the benefits and risks of aliskiren treatment: analyses of the 3A registry - Friedrich, S.; Zeymer, U.; Dechend, R.; Hagedorn, I.; Riemer, T.; Zemmrich, C.; Bramlage, P.; Pittrow, D.; Senges, J.; Schmieder, Roland (Journal of Human Hypertension, 2015)
We aimed to analyze benefits and risks of aliskiren treatment in older adults (?65 years) in clinical practice. Patients (n=14 986) were assigned to either aliskiren (ALIS), an angiotensin-converting-enzyme inhibitor or angiotensin receptor blocker (ACEi/ARB), or an agent not blocking the renin-angiotensin system (non-RAS). Older adults (n=7396) had a longer history of hypertension (8.7 vs 4.7 years; P<0.0001), lower mean diastolic blood pressure (DBP; 87.7±11.0 vs 92.1±11.0 mm Hg) and more renal (12.0 vs 5.6%; P<0.0001) or cardiovascular disease (44.0 vs 18.9%; P<0.0001); 4548 received aliskiren (68.8%), 1215 ACEi/ARBs (18.4%) and 850 non-RAS treatments (12.9%). Office BP at 1 year was reduced by 18.4±21.5/7.2±12.0 mm Hg. BP reductions were greater (19.5±21.7/7.6±12.1 mm Hg) in the aliskiren group than in the ACEi/ARB (15.6±20.9/6.4±11.9) and non-RAS groups (16.1±20.7/6.5±11.7 mm Hg), respectively (P<0.0001 for systolic BP (SBP) and <0.01 for DBP). After multivariable adjustment, differences in SBP reductions were clinically irrelevant and no differences were noted for DBP. Adverse effects were higher in older adults with no differences between treatment groups. In conclusion, the present analysis of a large, unselected cohort of patients in clinical practice from the 3A study, offers real-life evidence of the effectiveness and safety of aliskiren for the treatment of hypertension in older adults.
EVALuna2:3737